Leading edge erosion of wind turbine blades: Understanding, prevention and protection. (May 2021) - Mishnaevsky, Leon; Hasager, Charlotte Bay; Bak, Christian; Tilg, Anna-Maria; Bech, Jakob I.; Doagou Rad, Saeed; Fæster, Søren
Abstract: Surface erosion of wind turbine blades is one of rather critical problems of the wind energy development. In this overview paper, recent studies in the mechanisms, modelling and possibilities of preventing the surface erosion of wind turbine blades are discussed. Latest research in the area of leading edge erosion (LEE) from different viewpoints, based on meteorology, aerodynamics, materials science, computational mechanics are summarized. Technologies of experimental testing of anti-erosion coatings, effect of leading edge erosion on aerodynamics of wind turbines, roughness and its evolution are discussed, as well as meteorological aspects, parameters and characteristics of precipitation, possibilities of prediction of rain and hail and regional differences. Further, computational models of LEE and directions of the development of anti-erosion coatings are presented. Graphical abstract: Image 1 Highlights: Different approaches to control and prevent the erosion are presented. Blade surface erosion is triggered by voids and defects in the coatings. Predictive computational models of erosion are presented. Techniques of optimizing protective coatings are reviewed.